The application of silica and glass fibers in effective thermoinsulation of winter apparels - Yang, Guang (2019)
We studied the influence of silica and glass fibers on the properties of polyester non-woven padding, fixing interesting changes in thermoinsulation, thickness and stiffness of obtained composites. It was found that the combination of inorganic and polyester fibers allowed for obtaining improved thermoinsulating property, compared to non-woven materials based on individual fibers. The improvement is attributed to the enhanced reflectance and the decreased air permeability, which can reduce the heat lost through radiation and convection. The application of inorganic fibers also made the development of non-woven materials with small thickness, keeping thermoinsulating property similar or better, compared to the commonly used polyester non-woven padding. Furthermore, the designed non-woven composites in real models of winter jackets were evaluated in a climate chamber at -10 °C by infrared thermal camera. The results showed that the addition of inorganic fibers allowed the surface temperature of winter jackets more than 5 °C lower than that of winter jacket with pure polyester padding. They significantly enhanced the protection from cold and reduced heat loss from the human body.